1994
DOI: 10.1254/jjp.66.181
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Risperidone on Phencyclidine-Induced Behaviors: Comparison with Haloperidol and Ritanserin

Abstract: ABSTRACT-In this study, we investigated whether risperidone, a serotonin-S2A (5-HT21)/dopamine-D2 (D2)-receptor antagonist, inhibits phencyclidine (PCP)-induced stereotyped behaviors in comparison with haloperidol and ritanserin. Moreover, we also attempted to investigate the effects of these antipsychotics on the contents of dopamine, serotonin (5-HT) and their metabolites in rat striatum and frontal cortex. In rats, PCP (5 mg/kg, i.p.) caused hyperlocomotion and stereotyped behaviors, including sniffing, hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 32 publications
0
27
1
Order By: Relevance
“…One day after the last injection, they were placed individually in transparent acrylic cages (26 x 44 x 40 cm). Locomotor activity was recorded every 5 min for 30 min by digital counters with infrared cell sensors placed on the walls (SCANET SV-10, Toyo Sangyo Co. Ltd.) (Kitaichi et al, 1994).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One day after the last injection, they were placed individually in transparent acrylic cages (26 x 44 x 40 cm). Locomotor activity was recorded every 5 min for 30 min by digital counters with infrared cell sensors placed on the walls (SCANET SV-10, Toyo Sangyo Co. Ltd.) (Kitaichi et al, 1994).…”
Section: Resultsmentioning
confidence: 99%
“…Some authors Bleich et al, 1988;Janssen et al, 1988;Oka et al, 1993) have indicated that the 5-hydroxytryptaminergic system is involved in the negative symptoms of schizophrenia. It has been reported that PCP interacts with the 5-hydroxytryptaminergic system, since PCP has been shown to inhibit [3H]-spiperone binding to 5-HT2A receptors (Nabeshima et al, 1984a,b; and since PCP-induced behaviours are inhibited by 5-HT2A receptor antagonists such as ritanserin (Nabeshima et al, 1984c;1987;Kitaichi et al, 1994). In the present study, the enhancing effect of PCP on immobility was antagonized by ritanserin, risperidone, and clozapine, all of which show 5-HT2A receptor antagonistic properties (Janssen et al, 1988;Wilmot & Szczepanik, 1989;Oka et al, 1993;Kitaichi et al, 1994).…”
Section: Effects Of Antipsychotics On the Pcp-induced Enhancement Of mentioning
confidence: 99%
“…NMDA receptors in the brain of neonates, on the other hand, has been reported to inhibit nerve cell migration and the development of dendrites and realignment of synaptic junctions. 24,25) We demonstrated in the present study that neonatal PCP treatment on postnatal days 7, 9 and 11 (once a day at 10 mg/kg, s.c.) in mice enhanced susceptibility to PCP, a behavioral abnormality related positive symptom of schizophrenia, 26,27) impaired spatial working memory and social interaction behaviors in adulthood compared to saline-treated control mice. To examine whether such behavioral changes are due to PCP treatment during neurodevelopment, adult mice were treated with PCP (10 mg/kg, s.c.) 3 times every second day and subjected to the social interaction test.…”
Section: Discussionmentioning
confidence: 98%
“…Notably, the 5-HT 7 receptor antagonist SB-269970 did not modify the 5-HTP-induced HTR but prevented both the AS19-and fluoxetine-stimulating effects. Interestingly, various drugs with 5-HT 7 antagonistic activity, including atypical antipsychotics olanzapine and risperidone, antagonize HTR induced by 5-HTP or tryptamine (Kitaichi et al, 1994;Fu et al, 2000;Van Oekelen et al, 2002).…”
Section: Discussionmentioning
confidence: 99%